Jordanian children involvement within family consumption decision-making during COVID-19 - Huneiti, Kholod Saleh (Wiley, 2023)
The whole of society has been passing through difficult times due to the effects of COVID-19. Such a lengthy period has greatly impacted lifestyles and living standards. Accordingly, this paper aimed to examine the role of Jordanian children in purchasing decision-making within the framework of parental mediation during COVID-19. A quantitative methodology was applied, and a questionnaire targeted 287 children aged 8-12. Findings demonstrated a correlation between the influence of COVID-19. They changed the purchasing behaviour of children, as their daily habits have changed to increased periods of stay at home, leading to a long preoccupation with watching the Internet/commercials.
Keywords: Consumption decision-making; COVID-19; Information processing; Jordanian children; Parental mediation